DIVERSITY: RECOGNITION OF THE DIFFÉRANCE OR TOLERATED DIFFERENCE? A STUDY ON THE PERCEPTION OF MINING AND STEEL PROFESSIONALS - LORENTZ,CACILDA NACUR (2016)
ABSTRACT Purpose: To comprehend diversity on the organizational context. Originality/gap/relevance/implications: There are few critical studies on the subject, here grounded on the ideas of Derrida (2002) and on the theory of recognition of Honneth (2003). The comprehension of diversity is related to the construction of identity among individuals and refers to the concept of tolerance, enabling a discussion about recognition (or not) of differences. Key methodological aspects: Qualitative research, performed in organizations on the segments of mining and steel mill. Data were collected by focal groups submitted to discourse analysis. Summary of key results: It was found difficult to live with people of different groups. Diversity was also associated to difference and the topic recognition. It was evident that diversity should be managed in the organizational context, but the diversity that comes on the agenda of companies analyzed, including the HR practices, is the tolerable diversity. Key considerations/conclusions: Minority groups still lack of recognition, prevailing the valorization of a group over the others. To recognize differences is a challenging matter, considering the distance established between reflexive processes and the corporate practice. Finally, it is pointed out the need to promote actions that aim the equality of opportunities of treatment to the several groups present in the organization.